Dual oxidase 1 limits the IFNγ-associated antitumor effect of macrophages - Eric Deutsch; Michele Mondini; Pauline Hamon; Marine Gerbé De Thoré; Winchygn Liu; Lydia Meziani; Céline Clémenson; Ruy A Louzada; Raphaël Corre; Corinne Dupuy (Journal for ImmunoTherapy of Cancer)
Background Macrophages play pivotal roles in tumor progression and the response to anticancer therapies, including radiotherapy (RT). Dual oxidase (DUOX) 1 is a transmembrane enzyme that plays a critical role in oxidant generation.Methods Since we found DUOX1 expression in macrophages from human lung samples exposed to ionizing radiation, we aimed to assess the involvement of DUOX1 in macrophage activation and the role of these macrophages in tumor development.Results Using Duox1−/− mice, we demonstrated that the lack of DUOX1 in proinflammatory macrophages improved the antitumor effect of these cells. Furthermore, intratumoral injection of Duox1−/− proinflammatory macrophages significantly enhanced the antitumor effect of RT. Mechanistically, DUOX1 deficiency increased the production of proinflammatory cytokines (IFNγ, CXCL9, CCL3 and TNFα) by activated macrophages in vitro and the expression of major histocompatibility complex class II in the membranes of macrophages. We also demonstrated that DUOX1 was involved in the phagocytotic function of macrophages in vitro and in vivo. The antitumor effect of Duox1−/− macrophages was associated with a significant increase in IFNγ production by both lymphoid and myeloid immune cells.Conclusions Our data indicate that DUOX1 is a new target for macrophage reprogramming and suggest that DUOX1 inhibition in macrophages combined with RT is a new therapeutic strategy for the management of cancers.